2014
DOI: 10.1016/j.jns.2014.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Varicella zoster virus (VZV) in cerebral arteries of subjects at high risk for VZV reactivation

Abstract: With a decline in varicella zoster virus (VZV)-specific cell-mediated immunity, VZV can reactivate, infect cerebral arteries and cause stroke. Previous studies of cerebral arteries from subjects without a history of transient ischemic attacks or stroke revealed no VZV DNA or antigen; however, VZV DNA and antigen were found in the cerebral arteries of a subject with diabetes, a known risk factor for VZV reactivation and zoster. The present study analyzed an additional 55 cerebral arteries from 18 subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…(13) Most recently, additional analysis of 55 cerebral arteries from 18 subjects with co-morbidities that may increase the risk of VZV reactivation (i.e., a history of alcohol abuse, tricyclic antidepressant intoxication, cocaine abuse, HIV, or being over age 70) detected VZV antigen in 24/55 (44%) arteries from 14/18 (78%) subjects. (14) These findings support the notion that VZV infection of intracranial cerebral arteries may be a significant cause of stroke in the elderly, in HIV+ individuals, and other at-risk subjects.…”
Section: Co-morbidities That Increase Vzv Reactivationsupporting
confidence: 82%
“…(13) Most recently, additional analysis of 55 cerebral arteries from 18 subjects with co-morbidities that may increase the risk of VZV reactivation (i.e., a history of alcohol abuse, tricyclic antidepressant intoxication, cocaine abuse, HIV, or being over age 70) detected VZV antigen in 24/55 (44%) arteries from 14/18 (78%) subjects. (14) These findings support the notion that VZV infection of intracranial cerebral arteries may be a significant cause of stroke in the elderly, in HIV+ individuals, and other at-risk subjects.…”
Section: Co-morbidities That Increase Vzv Reactivationsupporting
confidence: 82%
“…The association of adventitial inflammation as a predictor of dolichoectasia in arteries with a thin media further supports the notion that HIV vasculopathy is a form of pathological brain arterial remodeling observed predominantly in HIV cases with persistent immunosuppression, in which adventitial inflammation may be either a surrogate of immunosuppression per se or a marker of the underlying pathophysiology leading to thinning of the media and subsequent arterial dilatation. We considered latent VZV as a potential antigenic stimulus in the arterial wall given evidence that latent VZV is frequently found in cases with HIV, but adjusting for latent VZV did not change the association between HIV infection and inflammation [28,29]. Infection of the arterial wall by HIV is, in our view, a plausible hypothesis that fits well the pattern and associations reported between HIV and brain arterial remodeling; however, it is a hypothesis that remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cerebral arteries from 4 diabetic subjects, who are at a higher risk for zoster and stroke (Heymann et al, 2008), revealed VZV DNA (3,740 copies per mg total DNA) in the artery of 1 subject; further analysis of 20 corresponding FFPE sections of this VZV DNA-positive artery revealed viral antigen in non-contiguous regions (skip lesions) of adventitia, with rare inflammatory cells immediately adjacent to viral antigen (Nagel et al, 2012). In another study, FFPE sections from 55 cerebral arteries from 18 subjects with co-morbidities that may increase VZV reactivation were obtained; immunohistochemical analysis of 10–12 sections from HIV-negative arteries and 2 sections from HIV-positive arteries detected VZV antigen in 44% arteries and 78% subjects with a history of alcohol abuse, tricyclic antidepressant intoxication, cocaine abuse, multiple myeloma, HIV and age >70 years (Nagel et al, 2014b). Of the 5 HIV+ subjects, 4 (80%) showed VZV antigen in arteries.…”
Section: Vzv In Normal Human Temporal Arteries and Intracerebral Amentioning
confidence: 99%